2013
DOI: 10.3791/50069
|View full text |Cite
|
Sign up to set email alerts
|

<em>C. elegans</em> Chemotaxis Assay

Abstract: Many organisms use chemotaxis to seek out food sources, avoid noxious substances, and find mates. Caenorhabditis elegans has impressive chemotaxis behavior.The premise behind testing the response of the worms to an odorant is to place them in an area and observe the movement evoked in response to an odorant. Even with the many available assays, optimizing worm starting location relative to both the control and test areas, while minimizing the interaction of worms with each other, while maintaining a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 13 publications
2
104
0
Order By: Relevance
“…The plates were incubated at 23°C in darkness for one hour. IJs were counted in the positive (host side) and negative (blank side) zones and then scored using a chemotaxis index [26]. The assay format was adapted from Grewal et al [1994] [27].…”
Section: Methodsmentioning
confidence: 99%
“…The plates were incubated at 23°C in darkness for one hour. IJs were counted in the positive (host side) and negative (blank side) zones and then scored using a chemotaxis index [26]. The assay format was adapted from Grewal et al [1994] [27].…”
Section: Methodsmentioning
confidence: 99%
“…A schematic of the four quadrants assay adapted from Margie et al (2013). For head avoidance assay, plates were divided into quadrants two test (A and D) and two controls (B and C).…”
Section: Figurementioning
confidence: 99%
“…For this reason, we treated male and female isopods separately. In order to test whether secretions act as a chemoattractant for C. elegans, adult male and female isopods were washed, and the wash solution was used to test chemoattraction in standard assays (Bargmann et al, 1993;Margie et al, 2013). Post-hoc Tukey's Honest Significant Difference (HSD) tests showed that neither N2 nor PB306 had a statistically significant attractive or repulsive behavior towards any isopod wash (Figure 1, Supplemental Table 1, Supplemental Table 2).…”
Section: Elegans Adults Are Not Attracted To Compounds From the Tementioning
confidence: 99%